Cercosporiosis resistance and cercosporin production in coffee genotypes - Ramos, Juliana Barros (2022)
Brown eye spot (BES), a disease caused by the necrotrophic fungus Cercospora coffeicola, leads to significant losses in coffee production. This disease causes damage to seedlings and adult plants, causing defoliation, in addition to impairing the quality of the beverage, due to the occurrence of lesions in the fruits. The fungus C. coffeicola produces cercosporin, a red toxin that is highly toxic to plant tissues. The control of BES is carried out through cultural practices and application of fungicides. However, the search for disease-resistant cultivars is characterized as a long-lasting and effective management method. Thus, this study aimed to evaluate the resistance of 60 coffee genotypes to BES, associating data on disease severity and heritability; to determine the levels of total soluble lignin and total soluble phenolic compounds in contrasting genotypes regarding disease susceptibility, in addition to quantifying cercosporin levels in leaves of Coffea arabica and C. canephora with symptoms of BES. For this, seedlings of 60 C. arabica genotypes from the Minas Gerais germplasm bank were inoculated with C. coffeicola isolates obtained from different coffee growing regions in Brazil. Disease severity was quantified using a diagrammatic scale, totaling five assessments. For the experiment to quantify the levels of total soluble phenolic compounds and soluble lignin, seedlings of the genotypes MG 1207 Sumatra (lower susceptibility to BES) and MG 0291 and Catuaí Vermelho IAC 144 (higher susceptibility to BES) were used. Leaf collections were performed at 24, 120, 240, 480 and 720 hours after inoculation with C. coffeicola. For the quantification of cercosporin, the genotypes of C. arabica (Mundo Novo 376/4, Catuaí Vermelho IAC 99, IPR 102, Topázio MG 1190) and C. canephora (Conillon clone 213) with leaf spot symptoms of BES. Cercosporin was quantified using high performance liquid chromatography (HPLC). The results showed that the population studied showed great genotypic (heritability) and phenotypic (severity of BES) variability. Severity values ranged from 2.37% (MG 1207 Sumatra genotype) to 32.02% (Catuaí Vermelho IAC 144) and individual heritability ranged from 29 to 88% among the 60 genotypes studied. The MG1207 Sumatra genotype showed partial disease resistance and high heritability, showing a potential source of resistance for coffee breeding programs. The levels of phenolic compounds showed variation in the three genotypes evaluated (MG 1207 Sumatra, MG 0291, and Catuaí Vermelho IAC 144) throughout the collection period. However, there was no relationship between the levels of phenolic compounds, lignin and resistance to BES, in the coffee genotypes. Cercosporin was detected in the leaves of cultivars Mundo Novo 376/4, Catuaí Vermelho IAC 99, IPR 102, Topázio MG 1190 and Conillon clone 213, indicating the presence of the toxin in leaf spot lesions. In addition, the efficiency of the HPLC method was verified for the quantification of cercosporin in coffee leaves.